YAP prevents premature senescence of astrocytes and cognitive decline of Alzheimer's disease through regulating CDK6 signaling. Issue 9 (20th August 2021) - Xu, Xingxing; Shen, Xiya; Wang, Jiaojiao; Feng, Wenjin; Wang, Mianxian; Miao, Xuemeng; Wu, Qian; Wu, Lihao; Wang, Xiaoning; Ma, Yimin; Wu, Shuang; Bao, Xiaomei; et al.
Abstract: Senescent astrocytes accumulate with aging and contribute to brain dysfunction and diseases such as Alzheimer's disease (AD), however, the mechanisms underlying the senescence of astrocytes during aging remain unclear. In the present study, we found that Yes‐associated Protein (YAP) was downregulated and inactivated in hippocampal astrocytes of aging mice and AD model mice, as well as in D‐galactose and paraquat‐induced senescent astrocytes, in a Hippo pathway‐dependent manner. Conditional knockout of YAP in astrocytes significantly promoted premature senescence of astrocytes, including reduction of cell proliferation, hypertrophic morphology, increase in senescence‐associated β‐galactosidase activity, and upregulation of several senescence‐associated genes such as p16, p53 and NF‐κB, and downregulation of Lamin B1. Further exploration of the underlying mechanism revealed that the expression of cyclin‐dependent kinase 6 (CDK6) was decreased in YAP knockout astrocytes in vivo and in vitro, and ectopic overexpression of CDK6 partially rescued YAP knockout‐induced senescence of astrocytes. Finally, activation of YAP signaling by XMU‐MP‐1 (an inhibitor of Hippo kinase MST1/2) partially rescued the senescence of astrocytes and improved the cognitive function of AD model mice and aging mice. Taken together, our studies identified unrecognized functions of YAP‐CDK6 pathway in preventing astrocytic senescence in vitro and in vivo, which may provide further insights and new targets for delaying brain aging and aging‐related neurodegenerative diseases such as AD. Abstract : YAP signaling is downregulated and inactivated in hippocampal astrocytes of aging mice and AD model mice, as well as in D‐gal‐ and PQ‐induced senescent astrocytes, in a Hippo pathway‐dependent manner. Mechanistically, YAP prevents the premature senescence of astrocytes through CDK6 signaling. Activation of YAP by XMU‐MP‐1 delays the senescence of astrocytes, and thereby improving the cognitive function of aged mice and AD model mice.